Efektivitas Model Psikoedukasi Terhadap Peningkatan Dukungan Keluarga Pada Pasien Skizofrenia: Studi Kuasi Eksperimental - Wahyu Kirana; Dewin Safitri; Yunita Dwi Anggreini (Malahayati Nursing Journal, 2026)
ABSTRACT Schizophrenia is a chronic psychotic disorder with a high risk of relapse, in which family support plays a crucial protective role. This study aimed to evaluate the effectiveness of a structured psychoeducation model in increasing family support as a relapse prevention measure in schizophrenia patients. The study used a quasi-experimental design with a pre-test and post-test approach without a control group. A total of 30 families of outpatients with schizophrenia at the West Kalimantan Provincial Mental Hospital were selected using a purposive sampling technique. The intervention consisted of a systematically developed psychoeducation model focusing on strengthening emotional, informational, instrumental, and reward support. Family support was measured using a questionnaire with proven validity and reliability with a Cronbach's Alpha of 0.935. Data were analyzed using the Wilcoxon Signed-rank test. The study showed a significant increase in family support after the intervention (p-value 0.05). These findings indicate that a structured psychoeducational model is effective in increasing family support as a relapse prevention measure in patients with schizophrenia. Keywords: Family Support, Psychoeducational Model, Schizophrenia.  ABSTRAK Skizofrenia merupakan gangguan psikotik kronis dengan risiko kekambuhan yang tinggi, di mana dukungan keluarga berperan sebagai faktor protektif penting.   Penelitian ini bertujuan mengevaluasi efektivitas model psikoedukasi terstruktur dalam meningkatkan dukungan keluarga sebagai upaya pencegahan kekambuhan pada pasien skizofrenia.Penelitian menggunakan desain kuasi eksperimental dengan pendekatan pre-test dan post-test without control group. Sebanyak 30 keluarga pasien skizofrenia rawat jalan di Rumah Sakit Jiwa Provinsi Kalimantan Barat dipilih menggunakan teknik purposive sampling. Intervensi berupa model psikoedukasi yang dikembangkan secara sistematis dengan fokus pada penguatan dukungan emosional, informasional, instrumental dan penghargaan. Dukungan keluarga diukur menggunakan kuesioner yang telah teruji validitas dan reliabilitas dengan Cronbach’s Alpha = 0,935. Analisis data menggunakan uji Wilcoxon Signed-rank. Hasil penelitian menunjukkan adanya peningkatan dukungan keluarga yang signifikan setelah intervensi (p value  0,05). Temuan ini menunjukkan bahwa model psikoedukasi terstruktur efektif meningkatkan dukungan keluarga sebagai upaya pencegahan kekambuhan pada pasien skizofrenia. Kata Kunci: Dukungan Keluarga, Model Psikoedukasi, Skizofrenia.